Tratamento diferenciado de temas de ciência, tecnologia e sociedade no currículo de ciências do ensino médio das Filipinas - Apler Bansiong; Rosemarie F Ocampo; Eartha Mae V. Caluza; Marife B. Rillera (Universidade Estadual de Alagoas, 2024)
Curriculum planners contend that the Science-Technology-Society (STS) Approach in Science instruction is one pedagogical practice leading to students' scientific literacy development - the overarching goal of science education.  This study assessed the treatment of STS themes in the Junior High School (JHS) science curriculum, as reflected in textbooks and practiced by science teachers.  Twelve textbooks (from two commercial publishers and the State Textbook Bureau) were analyzed for their treatment of 12 STS themes.  STS-related key concepts, terms, and illustrations were the units of analysis.  Meanwhile, the teachers' treatment was assessed through self - and student assessment.   Results showed that, as a whole, the STS themes emphasized in the textbooks and by the science teachers were consistent.  The two STS themes most emphasized are "Human Health and Diseases" and "Air Quality and the Atmosphere."  Conversely, "Nuclear Reactors" and "War Technology" are the topics least covered.  There was a differential treatment of the STS themes in the three textbooks regarding the STS-related key concepts, keywords, and illustrations.  The same differential treatment was observed across the four grade levels.   The curriculum implementers (i.e., the science teachers) recommended proper treatments of the STS themes.  Finally, a model was developed depicting the differential treatment of the STS themes in the junior high school curriculum.